TRADITION OR RELIGION? UNPACKING FEMALE CIRCUMCISION IN BUGIS-MAKASSAR CULTURE AND ISLAMIC LAW - Kasim, Amrah; Pallawagau, Baso; Sakka, Abdul Rahman; Abdillah; Rasna, Rasna (Al-Risalah, 2024)
This study focused on female circumcision as a sacred practice among the Bugis-Makassar community, intertwined with various cultural and religious beliefs. It drew attention from both Islamic law and Bugis-Makassar cultural perspectives. The objective was to explore scholars' views on female circumcision and its connection to Bugis-Makassar culture through a qualitative descriptive approach. Data collection methods included observation, interviews, and documentation. The findings indicated that within the context of Islamic law, female circumcision can be interpreted based on hadith and Sunnah, with varying opinions among Islamic scholars regarding its status as obligatory, recommended, or permissible, while some even oppose it. Despite these differing views, in communities like Bugis-Makassar, female circumcision is seen as an important cultural and traditional heritage. This practice was often accompanied by traditional ceremonies and religious rituals involving family and community. However, there were varied approaches to female circumcision within the Bugis-Makassar society, where some maintain this tradition with pride.